Skin Brightening Effects of Ascorbic Acid with ACTISOLV™ Integration: A Longitudinal Analysis Using Repeated Measures ANOVA - Amelia, Dita; Suliyanto, Suliyanto; Mahadesyawardani, Arinda; Azizah, Nur; Ariyawan, Jovansha; Adiputra, R. Arya Januarta; Adyatma, Irsyad Yoga (Jurnal Matematika, Statistika dan Komputasi, 2026)
Ascorbic Acid is a well-established active ingredient recognized for its efficacy in skin brightening and its antioxidant properties. However, its low chemical stability in cosmetic formulations remains a significant limitation. In response to this challenge, the patent-pending ACTISOLV™ formulation technology has been developed to enhance the stability of Ascorbic Acid, improving its resistance to oxidation and effectiveness in inhibiting melanin production. This study contributes to the advancement of sustainable cosmetic science through the development of more stable, eco-friendly, and sustainable skincare products. This study aimed to evaluate the longitudinal effects of a cream containing 20% Ascorbic Acid formulated with ACTISOLV™ on skin brightness. This study used longitudinal experimental data analyzed by Repeated Measures ANOVA. The results demonstrated a statistically significant increase in skin brightness over time (p-value = 0.000 < 0.05). Posthoc analysis revealed that skin brightness at weeks 6 and 12 differed significantly from baseline. However, no significant difference was found between the control and treatment groups and no significant interaction was observed between time and treatment group. These findings suggest that the observed improvement in skin brightness occurred similarly in both groups, indicating no additional effect attributable to the test formulation.